Anticancer effect of flaxseed and Cisplatin in oral squamous cell carcinoma: An in-vitro study (Journal of Medical Sciences, 2024)
Aims: oral squamous cell carcinoma (OSCC) is the most common form of oral cancer and is currently largely treated by surgery and/or radiation. Significant complications can occur because of these treatments. Adjunct therapies that are safer and less toxic are being explored. This study aims to investigate the potential anti-cancerous effect of the flaxseed on oral squamous carcinoma cells in vitro and determine the possible modulation of the activity of cisplatin by flaxseed using different durations of applications. Material and Methods: OSCC cell line cells were cultured and the MTT assay was used to assess cell metabolic activity.  Results: The antiproliferative effect of flaxseed oil at 24 and 48 hours as measured by the IC50 was 71.48±4.26 ug/ml and 18.11±1.36 ug/ml respectively. The mean percentage of viable cells at 24 and 48 hours when treated with flaxseed oil was 66.2+/-14.6 and 56.3+/-12.7, p-value